Front-Line ICI-Based Combination Therapy Post-TKI Resistance May Improve Survival in NSCLC Patients With EGFR Mutation - Tian, Tian; Yu, Min; Li, Juan; Jiang, Maoqiong; Ma, Daiyuan; Tang, Shubin; Lin, Zhiyu; Chen, Lin; Gong, Youling; Zhu, Jiang; Zhou, Qiang; Huang, Meijuan; et al. (Frontiers in Oncology, 2021)
Background Data on the use of immune checkpoint inhibitors (ICIs) in advanced non-small cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutation are limited. The current study aimed to assess the efficacy of ICIs in EGFR-mutant advanced NSCLC and explore the relevant influential factors. Materials and Methods Relevant clinical data of EGFR-mutant NSCLC patients who had received ICIs were collected from multiple hospitals. The primary endpoint was progression-free survival (PFS), and the secondary endpoints were overall survival (OS), objective response rate (ORR), and relevant influential factors. Results A total of 122 advanced EGFR-mutant NSCLC patients were included in the final analysis. The total cohort had an objective response rate (ORR) of 32.0%, a median progression-free survival (mPFS) of 5.0 months, and a median overall survival (mOS) of 14.4 months. Among 96 patients with common EGFR mutations (19Del, 52 patients; L858R, 44 patients), those who were administered front-line ICI exhibited better survival benefits than those who received later-line ICI after disease progression on tyrosine kinase inhibitors (TKIs) treatment (mPFS: 7.2 months vs. 3.4 months, respectively, P < 0.0001; mOS: 15.1 months vs. 8.4 months, respectively, P <0.0001). Moreover, the efficacy of ICI-based combination therapy was better than that of ICI monotherapy (mPFS: 5.0 months vs. 2.2 months, respectively, P = 0.002; mOS: 14.4 months vs. 7.0 months, respectively, P = 0.001). Multivariate analysis showed that ICI-based combination therapy and front-line ICI administration after progression on EGFR-TKI were associated with significant improvements in both PFS and OS (P < 0.05). A high PD-L1 expression (tumor proportion score, TPS≥50%) and the EGFR L858R mutation were only significantly associated with a better PFS (P <0.05). A better Eastern Cooperative Oncology Group (ECOG) status was independently associated with a favorable OS (P <0.05). Conclusions Taken together, combination immunotherapy in front-line was associated with improvement of survival in EGFR-mutant NSCLC patients post-TKI resistance. Further prospective studies with large sample sizes are required to identify the optimal combinatorial treatment strategy.